2014
DOI: 10.1088/2041-8205/792/2/l33
|View full text |Cite
|
Sign up to set email alerts
|

The Kozai-Lidov Mechanism in Hydrodynamical Disks

Abstract: We use three-dimensional hydrodynamical simulations to show that a highly misaligned accretion disk around one component of a binary system can exhibit global Kozai-Lidov cycles, where the inclination and eccentricity of the disk are interchanged periodically. This has important implications for accreting systems on all scales, for example, the formation of planets and satellites in circumstellar and circumplanetary disks, outbursts in X-ray binary systems, and accretion onto supermassive black holes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 49 publications
11
141
0
Order By: Relevance
“…The Kozai-Lidov mechanism induces antiphase oscillations in the orbital inclination and eccentricity of particles highly inclined to a binary companion (Kozai, 1962Lidov, 1962. Martin et al (2014) are the first to show that this process also occurs in a fluid disc. In our 60…”
Section: Fig 1 Shows the Simulation With An Initial Inclination Of 10mentioning
confidence: 90%
See 1 more Smart Citation
“…The Kozai-Lidov mechanism induces antiphase oscillations in the orbital inclination and eccentricity of particles highly inclined to a binary companion (Kozai, 1962Lidov, 1962. Martin et al (2014) are the first to show that this process also occurs in a fluid disc. In our 60…”
Section: Fig 1 Shows the Simulation With An Initial Inclination Of 10mentioning
confidence: 90%
“…The accretion rate is in code units of binary mass per binary dynamical time, and the time axis is in units of the binary dynamical time where a full orbit of the binary is 2π. Martin et al (2014) were the first to show that this behaviour occurs more generally for extended discs, and is therefore probably important in many astrophysical scenarios. The increase in accretion rate for the broken discs here is only a factor of a few, rather than the orders of magnitude found in Nixon et al (2013).…”
Section: Fig 1 Shows the Simulation With An Initial Inclination Of 10mentioning
confidence: 97%
“…In Martin et al (2014a), we found in simulations that gas capture by a binary companion appears to occur more easily if the disk is eccentric. Furthermore, substantially inclined disks can be subject to Kozai-Lidov oscillations that generate disk eccentricity (Martin et al 2014b). Consequently, the effects of disk inclination may naturally bring about additional effects due to disk eccentricity that in turn allows for greater disk extension.…”
Section: Discussionmentioning
confidence: 99%
“…Recently [92] performed simulations of the KL mechanism in hydrodynamical disks around a component of a binary system, finding oscillations of the inclination angle. The persistent m = 1 structure in the disks of models NC1 can be thought of as an eccentric distribution of matter.…”
Section: G Disk Twist and Tiltmentioning
confidence: 99%